The complete encyclopedia of sailing ships 2000 BC - 2006 AD - Batchelor, John; Chant, Christopher 1945- (Chartwell Books, 2006)
"A detailed look into the history and technical development of the sailing vessel from a primitive beginning right up to the present."--Dust jacket.